Change in Anemia by Carnitine Supplementation in Patients Undergoing Peritoneal Dialysis: A Retrospective Observational Study - Kaneko, Shohei; Yanai, Katsunori; Kitano, Taisuke; Miyazawa, Haruhisa; Hirai, Keiji; Ookawara, Susumu; Morishita, Yoshiyuki (Frontiers in Medicine, 2021)
Background: Carnitine supplementation improves various dialysis-related symptoms including erythropoietin-resistant anemia in patients who are undergoing hemodialysis. However, the utility of carnitine supplementation in patients who are undergoing peritoneal dialysis (PD) is not fully understood. Methods: Thirteen patients undergoing PD [mean age: 54.2 ± 14.8 years, males: 9/13 (69%)] administered oral carnitine supplementation (mean dose: 9.1 ± 3.3 mg/kg/day) for 4–6 months were retrospectively investigated. Changes in serum carnitine levels and other clinical variables including the erythropoietin resistance index (ERI) were analyzed after carnitine supplementation. Results: Carnitine supplementation increased serum total carnitine (48.5 ± 10.2 vs. 130.1 ± 37.2 µmol/L, P < 0.01), free carnitine (31.1 ± 8.3 vs. 83.1 ± 24.6 µmol/L, P < 0.01), and acyl carnitine (17.4 ± 2.8 vs. 46.9 ± 13.8, P < 0.01) levels. The acyl carnitine/free carnitine ratio was not affected (0.6 ± 0.1 vs. 0.6 ± 0.1, P = 0.75). Although the mean ERI was not affected by carnitine supplementation [13.7 ± 4.7 vs. 11.6 ± 3.4 IU/kg/(g/dL)/week, P = 0.28], the ERI change rate was significantly decreased (1.00 ± 0.00 vs. 0.87 ± 0.11, P < 0.01). Conclusion: Carnitine supplementation may improve erythropoietin resistance in patients who are undergoing PD.